THE EFFECT OF WORK STRESS AND WORKLOAD ON THE PERFORMANCE OF INPATIENT NURSES IN SURGICAL WARDS AND OBSTETRICS WARDS AT PKU MUHAMMADIYAH HOSPITAL KARANGANYAR, INDONESIA - Bakri, Fadel Firdaus; Sri Sundari; Qurratul Aini (International Journal of Innovative Technologies in Social Science, 2022)
This study aims to determine the effect of work stress and workload on the performance of inpatient nurses in the Surgical Ward and Obstetrics Ward at PKU Muhammadiyah Hospital, Karanganyar. The research approach used a quantitative approach with a cross sectional survey method. In this study, the population consisted of all inpatient nurses who worked in the Surgical Ward and Obstetrics Ward PKU Muhammadiyah Karanganyar Hospital, with a total sample size of 50 people. The normality test, multicollinearity test, and hypothesis testing were used in the data analysis. According to the findings of the study, work stress has a significant impact on the performance of inpatient nurses in the Surgical Ward and B at PKU Muhammadiyah Karanganyar Hospital (p < 5%). The higher the stress, the worse the performance of inpatient nurses in PKU Muhammadiyah Karanganyar Hospital’s Surgical Ward and Obstetrics Ward. The workload of nurses has a significant effect on the performance of inpatient nurses in the Surgical Ward and B at PKU Muhammadiyah Hospital Karanganyar (p < 5%). The higher the workload, the worse the performance of inpatient nurses in PKU Muhammadiyah Karanganyar Hospital’s Surgical Ward and Obstetrics Ward. Work stress and workload have a significant impact on employee performance at PKU Muhammadiyah Hospital Karanganyar, accounting for 71.7 percent of the total.